Nakayama Automorphism of Some Skew PBW Extensions (2019)
Let R be an Artin-Schelter regular algebra and A = σ(R)⟨x1,...,xn⟩ a graded quasi-commutative skew PBW extension over R. In this paper we describe the Nakayama automorphism of A using the Nakayama automor- phism of the ring of coefficients R. We calculate explicitly the Nakayama automorphism of some skew PBW extensions.